“Gobak Sodor” as A Suggestopedia Technique in Learning English in PAUD Ahmad Dahlan Surakarta - Indri Indri (International Journal of English Linguistics, Literature, and Education (IJELLE), 2022)
This study was a descriptive analysis that had a purpose to describe the application of suggestopedia in English learning in early childhood students (PAUD) through gobag sodor game. The data were taken through interview to English teachers of Ahmad Dahlan Kindergaten Surakarta and observation toward the process of English learning using gobag sodor. They were then analyzed using Milles and Huberman's interactive data analysis technique. The results of this study showed that the application of gobag sodor in English learning in Ahmad Dahlan Kindergarten was in line with the suggestology or suggestopedia method in which it eradicated the feelings of fear of making mistakes, fear of being incompetence, and fear of something new or unfamiliar that made the students got rilex and happy in learning foreign language such as English. It was considered beneficial because it involved the physical, psychological and knowledge aspects of the students and teachers. Then,  it should be the disadvantages of teaching English using the Gobak Sodor game are pedagogic skills and the teacher's special attention to early childhood in preparing Gobak Sodor teaching and learning activities.